UNSUR PERSAMAAN PADA POKOKNYA DALAM PERKARA PEMBATALAN MEREK TERDAFTAR (STUDI KASUS MEREK PT. KRAKATAU STEEL DAN MEREK PT. PERWIRA ADHITAMA SEJATI) - MELLISA YANWAR (PREMISE LAW JURNAL, 2016)
Brand registration provides exclusive right and legal protection and certainty for the first owner of brand registration. Even though brand has been registered in the Directorate General of HKI; in practice, other people always imitate the brand or register a brand which has similar in substance to the previous registered brand. The problems of the study were as follows: how about the status of a registered brand which was similar in substance to the previous registered brand, how about the legal responsibility of the Directorate General of HKI on registering a brand which was similar in substance to the previous registered brand, and what attempts were made by the owner of the brand to protect him when there was a registration of a brand which has similar to the previous registered brand. The study used normative research method. Keywords: Similarity in Substance, Brand Registration, Previous Registered Brand, Legal Responsibility, Legal Protection, PT. Karakatau Steel, PT. Perwira Adhitama Sejati